Análise do transporte rodoviário de produtos perigosos classe 1 – explosivos: uma abordagem utilizando o método fuzzy AHP - Andrade, Winston Aparecido (2024)
Road transport represents 61.1% of freight transport, with a length of 1,721,342 kilometers of the national road network. ANTT regulates the land transport of goods and products within Brazilian territory, including dangerous products, in accordance with legislation. Important sectors of the economy such as mining, the oil and gas industry, the military industry and public security share the use of explosive products and their derivatives, explosives belong to class 1 of dangerous products and are divided into six subclasses, according to the classification of the United Nations (UN). The systematic review of the literature revealed the lack of specific research for this category, mainly on the transport of explosives. While there are studies on dangerous products in general, the specific approach to explosive products is limited. Thus, in this research investigates the road transport of explosive products, aiming to identify, categorize and hierarchize the risk factors in the transport of explosives, in addition to establishing an interdependence oh the connection between the most relevant factors, within the context of a multi-criteria decision analysis. The application of the Delphi method seeks to identify relevant criteria to exclude less significant factors. The use of the FUZZY AHP (FAHP) method provides a flexible and comprehensive approach, considering the uncertainty of this context. The research fills a gap in the academic literature on risk management in the transport of explosive products, offering specific material to an area lacking detailed investigation. In practical terms, the results are interesting for the transport industry, regulators and change this, as they can contribute to strategic decision-making and the improvement of safety policies.